Implementasi Algoritma FP Growth Untuk Menganalisis Pola Pembelian Konsumen Balcos Compound - Khadijah, Ayu Suci; Waluyo, Anita Fira (STMIK Banjarbaru, 2024)
This study analyzes consumer purchasing patterns at Balcos Compound coffee shop using the FP-Growth algorithm. The data used includes 2,438 sales transactions for one month, with minimum support parameters of 5% and minimum confidence of 80%. The results of the analysis show a significant association pattern between the purchase of 600ml Mineral Water and Lemon Tea, with support of 0.0029, confidence of 100%, and lift of 0.9752. Comparative tests with one-week data produce a similar pattern, with support of 0.0062, confidence of 100%, and lift of 0.6211. These findings serve to formulate a more optimal marketing strategy, for example through product bundling offers and combined transaction discounts. This study is expected to increase sales and customer satisfaction in coffee shops..Keywords: Purchasing patterns; FP-Growth algorithm; Marketing strategies; Coffee shopÂ AbstrakPenelitian ini menganalisis pola pembelian konsumen di kedai kopi Balcos Compound menggunakan algoritma FP-Growth. Data yang digunakan mencakup 2.438 transaksi penjualan selama satu bulan, dengan parameter minimum support 5% dan minimum confidence 80%. Hasil analisis menunjukkan pola asosiasi yang signifikan antara pembelian Mineral Water 600ml dan Lemon Tea, dengan support 0,0029, confidence 100%, dan lift 0,9752. Uji banding dengan data satu minggu menghasilkan pola serupa, dengan support 0,0062, confidence 100%, dan lift 0,6211. Temuan ini berfungsi merumuskan strategi pemasaran yang lebih optimal, misalnya melalui penawaran bundling produk dan diskon transaksi gabungan.Penelitian ini diharapkan dapat meningkatkan penjualan dan kepuasan pelanggan kedai kopi.Â